APTOPUS LATERALIS (CARDIOPHORINAE, ELATERIDAE, COLEOPTERA, INSECTA). REDESCRIPCIÓN Y NUEVAS ESPECIES - Aranda, Susana G. (Instituto de Ecología, A.C., 2003)
In this work, Aptopus lateralis (Erichson) is redescribed and the Champion´s varieties "ß" and " ?" are described as new species. Illustrations of the habitus and the genitalia of the three analized species are included.